2012
DOI: 10.1093/geronb/gbs052
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function as a Prospective Predictor of Falls

Abstract: Although cognitive measures at baseline were significantly associated with falls and recurrent falls at follow-up, these measures did not predict falling after considering known risk factors of falls and psychomotor speed. Thus, it may be that simple measures of psychomotor speed are more salient predictors of falls than cognitive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 57 publications
2
29
0
4
Order By: Relevance
“…Ninety days after hospital discharge, the independent factors were female gender with age ≥80 years and femoral neck fracture, which showed a 46 times greater chance of loss of functionality. These results are similar to the results of studies that have shown a predominance of elderly women, 70 or older, fall victims [1,2,[22][23][24][25][26][27], TBI [24,28] and associated comorbidities [25,29,30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ninety days after hospital discharge, the independent factors were female gender with age ≥80 years and femoral neck fracture, which showed a 46 times greater chance of loss of functionality. These results are similar to the results of studies that have shown a predominance of elderly women, 70 or older, fall victims [1,2,[22][23][24][25][26][27], TBI [24,28] and associated comorbidities [25,29,30].…”
Section: Discussionsupporting
confidence: 89%
“…However, the psychomotor reaction speed of individuals who have some difficulty with postural balance may be considered an important predictor of falls, as it is directly related to the responsiveness of the elderly at the time of the trauma event [27]. In this context, the maintenance of appropriate social activity after the occurrence of femoral fracture as a result of a fall represents a challenge for health professionals.…”
mentioning
confidence: 99%
“…34,35 Por otro lado, se ha visto también que el incremento en la actividad física puede impactar positivamente en la disminución de la frecuencia de caídas. 33 Finalmente, tanto en nuestro país como a nivel internacional se han desarrollado guías clínicas para el abordaje del síndrome de caídas.…”
Section: Sí Nounclassified
“…It leads to physical and psychological trauma. It is one of the leading causes of death due to unintentional injuries among older adults [3]. Falls are a major cause of morbidity among older adults, especially for those with cognitive problems [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that identifying risk factors of falling followed by proper interventions can successfully reduce the incidence of falling. It is, therefore, important to understand the risk factors for falling in order to promote falls prevention and improve public health [3].…”
Section: Introductionmentioning
confidence: 99%